Recombinant-activated factor VII for control and prevention of hemorrhage in nonhemophilic pediatric patients - Ampaiwan Chuansumrit (2018)
A total of 108 episodes among 103 nonhemophilic pediatric patients (nine newborns, 16 infants and 78 children) treated with recombinant factor-activated VII (rFVIIa) were evaluated retrospectively. These episodes were divided into two groups: group 1 included 86 occurrences for hemorrhagic control of ongoing massive bleeding due to thrombocytopenia and coagulopathy unresponsive to blood component therapy in patients with dengue hemorrhagic fever, life-threatening, intraoperative and postoperative bleeding; group 2 included 22 episodes for prevention of hemorrhage with invasive procedures in patients with chronic liver disease and associated coagulopathy, and patients without preexisting hemostatic disorder but at high risk due to their underlying diagnosis and required surgical intervention. The effective control of hemostasis response rate in group 1 was significantly lower than in group 2. The median total dose per kilogram of rFVIIa group 1 was twice that of group 2. The overall case-fatality rate related to bleeding or underlying conditions was 31.1% (32/103). Adverse events were observed in three patients (2.9%) receiving rFVIIa for control of intraoperative and postoperative bleeding in the setting of corrective cardiac surgery. These results support the safety and potential benefit of rFVIIa for control and prevention of hemorrhage in pediatric patients without congenital hemophilia. © 2010 Wolters Kluwer Health | Lippincott Williams & Wilkins.